Serviços ecossistêmicos e conhecimento ecológico local em lagos naturais do semi-árido do Brasil - Lima, Francisco Hélio Coelho de (2022)
People have used lagoons as natural capital for centuries, benefiting both from productsderived from biodiversity and using water for subsistence – benefits that are known asecosystem services (ESs). Consequently, the use of lagoons by humans alters the biodiversityand quality of these reservoirs, potentially decreasing the provision of services. However, thisfeedback depends on how people perceive and use the ponds – factors that vary from year toyear and are not integrated into most studies. Thus, we seek to understand (i) how populationsliving around natural lakes perceive and use ecosystem services and (ii) how seasonal watervariation affects the use and occupation around lakes and affects biodiversity and the qualityof the water. Water. We evaluated lakes in different phytoecological regions of the semiaridlandscape and analyzed local ecological knowledge (LEK) about services in humansettlements around the lakes through participant observation and semi-structured interviews.For the first objective, we identified the services indicated by the individuals and then applieda water quality index for the ponds. People identified a variety of ESs and variation in waterquality. In the second objective, our hypothesis was that the dynamics of water fluctuationalters the use and occupation of local populations and alters the biodiversity of fish,macrophytes and water quality. To do so, we analyzed eleven aquatic variables, sampled fish,macrophytes and identified the use and occupation of their surroundings in loco and droneimages. We sampled response variables at four times of the year, according to seasonality. Theresults indicate that the use and management varied around the ponds and were influenced bythe seasonality of the water, with periods of the year with greater influence on biodiversityand water quality. At the same time, water quality varied between periods and between lakes.We identified that local populations understand the importance of the services provided by thelagoons, both for their cultural identity and for their subsistence. However, we observed thatthe indicators of biodiversity and water quality varied with the seasonality of the volume ofwater in the lakes, indicating a factor of fluctuation of ecosystem services throughout the year.Therefore, management strategies must integrate local ecological knowledge and indicators ofbiodiversity and water quality to maximize ecosystem services provided to humanpopulations.